2021
DOI: 10.32725/det.2021.011
|View full text |Cite
|
Sign up to set email alerts
|

Post-Millennial Visegrád Four Geopolitics: Illiberalism and Positionality within the EU

Abstract: This research paper analyses shifts in the Visegrád Group's (Czechia, Hungary, Poland and Slovakia) identity as a regional integration platform and, in particular, links between Europeanization, illiberalism and V4 geopolitical identity. This provides a background for investigating contested ideas of European integration that discursively frame Central Europe's 'illiberal regionalism'. I suggest that this regionalism does not represent a coherent or stable political project. Tensions involved in this regionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
0
0
Order By: Relevance
“…The region has undergone socio-spatial differentiation and economic convergence, with areas in Central and Eastern Europe experiencing catch-up in the convergence process. Fiscal decentralization has been linked to economic growth rates across 16 Central and Eastern European countries, including Albania, Bulgaria, Croatia, the Czech Republic, Hungary, Poland, Romania, Slovakia, and Slovenia [44][45][46]. The study found that sub-national expenditure and transfers had a negative correlation with national growth rates in the region, while locally imposed taxation showed mildly positive economic benefits over time.…”
Section: Development Of the Post-socialist Regionsmentioning
confidence: 88%
“…The region has undergone socio-spatial differentiation and economic convergence, with areas in Central and Eastern Europe experiencing catch-up in the convergence process. Fiscal decentralization has been linked to economic growth rates across 16 Central and Eastern European countries, including Albania, Bulgaria, Croatia, the Czech Republic, Hungary, Poland, Romania, Slovakia, and Slovenia [44][45][46]. The study found that sub-national expenditure and transfers had a negative correlation with national growth rates in the region, while locally imposed taxation showed mildly positive economic benefits over time.…”
Section: Development Of the Post-socialist Regionsmentioning
confidence: 88%